Relationship between outcome scores and knee laxity following total knee arthroplasty: a systematic review - Kappel, Andreas; Laursen, Mogens; Nielsen, Poul T; Odgaard, Anders (Acta Orthopaedica, 2018)
Background and purpose — Instability following primary total knee arthroplasty (TKA) is, according to all national registries, one of the major failure mechanisms leading to revision surgery. However, the range of soft-tissue laxity that favors both pain relief and optimal knee function following TKA remains unclear. We reviewed current evidence on the relationship between instrumented knee laxity measured postoperatively and outcome scores following primary TKA. Patients and methods — We conducted a systematic search of PubMed, Embase, and Cochrane databases to identify relevant studies, which were cross-referenced using Web of Science. Results — 14 eligible studies were identified; all were methodologically similar. Both sagittal and coronal laxity measurement were reported; 6 studies reported on measurement in both extension and flexion. In knee extension from 0° to 30° none of 11 studies could establish statistically significant association between laxity and outcome scores. In flexion from 60° to 90° 6 of 9 studies found statistically significant association. Favorable results were reported for posterior cruciate retaining (CR) knees with sagittal laxity between 5 and 10 mm at 75–80° and for knees with medial coronal laxity below 4° in 80–90° of flexion. Interpretation — In order to improve outcome following TKA careful measuring and adjusting of ligament laxity intraoperatively seems important. Future studies using newer outcome scores supplemented by performance-based scores may complement current evidence.